Legal review of artificial intelligence-based autopilot electric vehicles in Indonesia - Kusuma, Brata; Wardhani, Novea Elysa; Kristanto, Kiki (Journal of Law Science, 2025)
The rise of electric vehicles using AI technology and Autopilot mode has potential benefits and issues in Indonesia's transportation system. These cars are more energy efficient and safe to drive. Yet, the legality of autonomous electric cars is still unclear due to lacking regulations. This article explores the legal concerns of AI-driven electric vehicles, such as safety standards, liability in accidents, and data privacy. This study employs a normative legal research method with legislative and conceptual approaches to analyze various applicable regulations, such as Law Number 22 of 2009 concerning Traffic and Road Transportation and Presidential Regulation Number 55 of 2019 concerning Battery-Based Electric Vehicles. The research findings indicate that despite some rules that can serve as a basis for regulation, there are still legal loopholes that need to be addressed promptly. The government needs to formulate specific regulations covering safety aspects, feasibility tests, and mechanisms of legal responsibility in accidents involving autonomous vehicles. Additionally, user data protection must be reinforced to prevent the misuse of information collected by AI systems. In conclusion, strict regulations are needed to ensure that technological advancements can move forward while safeguarding safety and legal certainty for the public. This research encourages new regulations governing security aspects, legal responsibility, and data protection in AI-based autopilot electric vehicles to address legal gaps in the Road Traffic and Transport Law (LLAJ) and the Electronic Information and Transactions Law (ITE).